(68Ga)Ga-FAPI-46 PET/MRI for therapy monitoring of desmoid tumors - Hinterberger, Anna; Jakob, Jens; Menge, Franka; Davarci, Güllü; Grawe, Freba (Clinical nuclear medicine, 2026)
Desmoid tumors (DT) are locally aggressive and show a high potential for recurrence. Magnetic resonance imaging (MRI) is the preferred modality for DT staging due to its high soft-tissue contrast. However, MRI was found to have limitations for therapy monitoring. Due to the high expression of fibroblast activation protein (FAP) in desmoid tumours, positron emission tomography (PET) with FAP inhibitors (FAPI) can serve as an excellent modality for visualizing DT activity. Here, we present the case of a patient with DT undergoing therapy, demonstrating that [68Ga]Ga-FAPI-46 PET holds promise for a more precise therapy monitoring.